Analysis of ecosystem services provision in the Colombian Amazon using participatory research and mapping techniques - Ramírez Gomez, Sara; Torres Vitolas, Carlos A.; Schreckenberg, Kate; Honzák, Miroslav; Cruz García, Gisella S.; Willcock, Simon P.; Palacios, Erwin; Pérez Miñana, Elena; Verweij, Pita; Poppy, Guy (Elsevier, 2015)
Over the last two decades indigenous peoples in the lower Caquetá River basin in Colombia have experienced detrimental changes in the provision of important ecosystem services in ways that have significant implications for the maintenance of their traditional livelihoods. To assess these changes we conducted eight participatory mapping activities and convened 22 focus group discussions. We focused the analysis on two types of change: (1) changes in the location of ecosystem services provisioning areas and (2) changes in the stock of ecosystem services. The focal ecosystem services include services such as provision of food, raw materials and medicinal resources. Results from the study show that in the past two decades the demand for food and raw materials has intensified and, as a result, locations of provisioning areas and the stocks of ecosystem services have changed. We found anecdotal evidence that these changes correlate well with socio-economic factors such as greater need for income generation, change in livelihood practices and consumption patterns. We discuss the use of participatory mapping techniques in the context of marginalized and data-poor regions. We also show how this kind of information can strengthen existing ecosystem-based management strategies used by indigenous peoples in the Colombian Amazon.